KRISIS PANGAN DUNIA: REVITALISASI NEO FUNGSIONALISME - Effendy, Tony Dian (Jurnal Bestari, 2008)
Food problem in fact has been predicted since ten years ago. Yet it does not gain any response. The problem appears to be uncontrolled as the food crisis has influenced three factors: world population and agriculture production, poverty and hunger, and economic policy. Neo liberalism has the mechanism that should be responsible to these crises. In its free market mechanism, a state has to try to achieve full productivity and comparative advantages. The result was that the agriculture sector would change to be industrial sector. In term of international studies, there was one approach to answer this problem, which was neo functionalism. It mentioned that every state should build international cooperation and pay attention more on food crises. This mechanism played by the international organization, FAO. However, there were scepticisms concerning to this approach because of the worry of the domination of developed countries. It meant that there were dependent targets. Localism was one of solution but it could not walk alone; it needed international cooperation to support this localism bringing back the agricultural production to the main function as the food suppliers.